Developing quality reading instruction through a contextual approach in the English Language Education - Sinaga, Tuntun; Riyantika, Fajar; Puteri, Celiacika Gustisiwi (Aksara: Jurnal Bahasa dan Sastra, 2023)
The problems discussed in this study are related to the development of the quality Reading instruction through a contextual approach for students of English language program. The purpose of the study is to improve the quality of Reading learning through a contextual approach to students of the English Language Education Study Program, FKIP, University of Lampung. This research employed Class Action Research (CAR) which is intended to provide information on how to take appropriate actions to improve student activities in the learning process with a contextual learning approach that has an impact on increasing student learning achievement. The results showed that the quality of Reading learning increased through a contextual approach in the English Language Education Study Program students. In the first cycle, the average achievement score stands at 62.4, which then rises to 68.7 in the second cycle, and further increases to 77.2 in the third cycle. This proves that the use of a contextual approach is able to improve the quality of reading learning for English Language Education Study Program students, FKIP, University of Lampung.